Cantilever Type Retaining Wall Design - Imron Rusadi; Era Agita Kabdiyono (Jurnal Ilmiah Teknik, 2025)
Retaining walls are a crucial soil control technique for mitigating landslides. The slope conditions at the Karawang site are considered unstable. The purpose of this study is to analyze the design of retaining walls at this location using cantilever retaining walls and manual calculations. Data collection techniques include literature review. The analysis results show that the dimensions of the cantilever retaining wall with dimensions of the total height of the DPT = 3.50 m, the total width of the DPT foundation = 3.80 m, the wall thickness = 0.40-0.60 m, the diameter of the main reinforcement used, D = 19 mm, the diameter of the shrinkage reinforcement used, D = 13 mm, the thickness of the concrete cover, s = 40 mm. Based on the soil profile at the location, the soil behind the DPT wall of the original soil does not meet the safety factor, Volume weight (γ1) = 16.7 kN / m3, Internal friction angle, (φ1) = 15.21 º, Cohesion (c1) = 5.7 kN / m2, so it is necessary to replace the granular soil at the back of the DPT to Volume weight (γ1) = 18.5 kN / m3, Internal friction angle (φ1) = 33 º, Cohesion (c1) = 4.16 kN/m2,